NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR NEGERI 159 PALEMBANG - Wulan Hafisa Putri; Trika Nur Fadillah; Mirta Antalika; Ines Tasya Jadidah (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
This research was conducted with observational thinking about the application of character education values in social considering learning at the 159 Palembang State Elementary School. This research uses an expressive qualitative design with a substance testing method. Based on the discourse and discourse, it is stated that: 1) Preparation for the implementation of character education at SD Negeri 159 Palembang consists of the stages of taking: planning, implementation, and assessment; and 2) the suitability of topical books that are in accordance with character education including religion, noble character, resilience, teaching, imaginative, fair, curiosity, national spirit, respect for achievement, communicative neighbors, care for the environment, social care, love to study, attentive, respect the country, work hard, and be independent